Quality of life and severity of skin changes in the dynamics of psoriasis - Owczarek, Krzysztof; Jaworski, Mariusz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : Psoriasis is a chronic skin disease with periods of recurrence and remission. The skin changes which are typical of this disease can have a considerable effect on the patient’s psychological state, self-esteem and body image. It can also affect the patient’s functioning in all areas of life and quality of life. Aim : The present study characterized the patient needs to improve the quality of life in specified areas in patients depending on the severity of psoriatic changes. Material and methods: The study was conducted in two stages on 100 patients aged from 18 to 66. A dermatological examination was conducted in stage one. Patients’ dermatological condition was assessed with the Psoriasis Area and Severity Index (PASI). Clinical and socio-economic information was collected in stage two using a questionnaire, a medical interview and a standardized questionnaire measuring quality of life, the WHOQOL-BREF. Results: The following factors had the greatest effect on the general quality of life and quality of health ratings in the studied sample: severity of psoriatic changes, duration of the most recent recurrence and sex. Severity of psoriatic changes had a negative effect on the patient’s somatic, psychological, environmental and social functioning. Duration of the most recent recurrence had a negative effect on social functioning. Practical implications of this study allow dermatologists to determine the appropriate therapeutic intervention which improves the quality of life of these patients on the one hand, and will increase patient’s involvement in the process of treatment on the other hand. Conclusions : Quality of life is more impaired by more severe chronic skin disease.